Non-tuberculous long multi-segment spinal epidural abscess with co-existing giant psoas abscess in an intravenous drug abuser: A rare case report from India - Mishra, Manish Kumar; Pandey, Nityanand (Nepal Journal of Neuroscience, 2023)
In developing countries, Mycobacterium tuberculosis is rampant and it’s the first differential in causation of spinal epidural abscess (SEA) and/or, psoas abscess (PA). This microbiota pertaining to these diseases, is in contrast with that of developing nations, where it is primarily bacterial. The burden of intra-venous drug abusers is very high in India, however there is corresponding rarity of intra-venous drug abuse (IVDA) related SEA/ PA case studies. Even at global scale, there is no fixed recommendation in the surgical management (instrumentation and fusion) of IVDA-SEA subset of patients owing to their low volume and poor-follow-up. In this back-ground authors present their experience of managing an IVDA associated long segment multi-level SEA with giant PA who presented with ASIA Grade-C neurological deficit.